A 'Turn to Language' as a Response to the Shifting Contours of Racist Discourse. Issue 3 (27th May 2017) - Masocha, Shepard
Abstract : Racist discourse has significantly shifted away from the use of overt racial language and has predominantly become a coded and subtle discourse. This article highlights how paying attention the ways in which language is used in its social and cognitive contexts can provide social work with a more robust response to the shifting parameters of racist discourse. It illustrates how using a strand of discourse analysis called discursive psychology can result in an enhanced understanding of the ways in which exclusionary sentiments are couched in contemporary discourses. Drawing on data from a minority of social workers who participated in a wider study that explored the experiences of social workers who were working with asylum seekers in a UK local authority, the article highlights the ways in which exclusionary views can be articulated and legitimated by drawing on culture, instead of race, as a marker of difference. It is suggested that a turn to language can result in significant enhancements to current antiracist frameworks.